2003
DOI: 10.1292/jvms.65.1167
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistolocalization of Carbonic Anhydrase Isozyme (CA-VI) in Bovine Mammary Glands

Abstract: ABSTRACT. The localization of bovine carbonic anhydrase isozyme VI (CA-VI) was examined immunohistochemically in bovine mammary glands during early lactation period (after 2-3 days of postpartum) and dry period (at about 2 months preparturition in adu lts), and young calves (at 30 and 150 days after birth) using specific CA-VI antiserum. The immunoreaction for anti-CA-VI antiserum was very weak in the mammary glands in young (prepubescent) calves. In dry period, CA-VI was also weakly expressed in secretory epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…CA may play an important role in the development of mammary gland and milk secretion. In fact, it has been reported that the distribution, expression, and concentration of CA VI in bovine mammary gland and colostrum have been reported [6]. In this study the expression of CA II, IV and IX were shown in the normal mammary gland tissue.…”
Section: Discussionmentioning
confidence: 51%
“…CA may play an important role in the development of mammary gland and milk secretion. In fact, it has been reported that the distribution, expression, and concentration of CA VI in bovine mammary gland and colostrum have been reported [6]. In this study the expression of CA II, IV and IX were shown in the normal mammary gland tissue.…”
Section: Discussionmentioning
confidence: 51%
“…, Motoharu OISHI 1) , Tomoko AMASAKI 4) , Satoshi SOETA 5) , Nobutsune ICHIHARA 1) , Toshiho NISHITA 2) , Masaru MURAKAMI 3) , Hajime AMASAKI 5) and Masao ASARI 1) * 1) Departments of Anatomy, 2) Carbonic anhydrase (CA; EC4.2.1.1) is a zinc-containing metalloenzyme that has many functions, including macromolecule stabilization, gas exchange, acid-base balance, ion transport, and bone resorption [17]. About 14 CA isoenzymes are widely distributed in almost all mammalian species [4].…”
mentioning
confidence: 96%
“…CA-II is the most common CA family and these enzymes exhibit high catalytic activity in erythrocytes, liver, pancreas and kidney cells [15], and in the cells of the parotid and submandibular glands [13]. CA-VI is one of the secreted-type CAs, and has been detected in the salivary glands [6], mammary glands [5] and lacrimal glands [11].…”
mentioning
confidence: 99%
“…Of these isoenzymes, only CA-VI occurs in secreted form, and it localizes to the digestive organs, specifically the parotid, submandibular and esophageal, lingual serous von Ebner's glands in sheep [8,9,31], rats [7,18,23], humans [13,18,20,24,29] and dogs [2,14,21]. Furthermore, the CA-VI isoenzyme has been identified in the lacrimal and mammary glands of rats [26], sheep [25] and cattle [12,16]. The CA-VI secreted in mammary glands regulates acid-base balance of upper alimentary canal [12].…”
mentioning
confidence: 99%
“…Furthermore, the CA-VI isoenzyme has been identified in the lacrimal and mammary glands of rats [26], sheep [25] and cattle [12,16]. The CA-VI secreted in mammary glands regulates acid-base balance of upper alimentary canal [12]. Highly concentrated buffer ions are important for mucosal protection against an excessively acidic milieu.…”
mentioning
confidence: 99%